Cataloging for a Celebration: Metadata for an Institutional Repository from the Ground Up. Issue 2 (17th February 2022) - Cho, James H.
Abstract: The Adelphi University Libraries recently adopted Esploro as its institutional repository. By engaging in a pilot project, cataloging assets for Adelphi's Celebration of Scholarly Research and Creative Works, the Catalog and Metadata Strategies Unit created metadata for this collection from the ground up. We looked at workflows, automated processes, cataloging oversight, and the limitations of Esploro. We determined that authority control for both name and subject was essential to an effective institutional repository. This case study illustrates how the drawbacks of our institutional repository led us to find local solutions to serve the needs of our users.